Evaluation of Whole Cottonseed Intake and in Situ digestibility in Beef Cattle. (7th May 2021) - Jacobs, Luke L; Mullenix, Kim K; Muntifering, Russell B; Dillard, S Leanne L; Carrell, Russell C
Abstract: Whole cottonseed (WCS) is a byproduct of the cotton industry and can be used to supplement protein and energy to beef cattle. Given rapid industry changes in cotton variety use and their influence on WCS size, density, and quality characteristics, periodic evaluation of cotton byproducts is needed to determine appropriate feeding strategies. The objective of this study was to evaluate total WCS intake, gossypol intake, and digestibility of a widely-planted common variety of WCS in the southeastern U.S., Delta Pine 1646 (DP1646), compared with a low-gossypol variety, Ultra-Low Gossypol Cottonseed (ULGCS). Six Angus and Angus-cross calves (two steers and one bull per group) were used in a 28-day feeding trial in a crossover design. Each group was fed either DP1646 or ULGCS for a 7-d acclimation period followed by a 7-d measured intake period. Treatment groups were then switched to the other variety for a second acclimation and measured period. Intake was greater (P = 0.0011) for ULGCS than for DP1646, with an average intake of 2.20 ± 0.24 kg and 1.06 ± 0.24 kg, respectively. Free gossypol intake was not different (P = 0.9371) among treatments with an average daily intake of 13 ± 0.1 ppm and 2 ± 0.8 ppm for DP1646 and ULGCS, respectively. An in situ digestibility trial was conducted using two ruminally-cannulated steers to compare the 72-h digestibility of DP1646 and ULGCS. There were no differences (P = 0.5910) between treatments in total DM digestibility between WCS varieties or treatment by time interaction (P = 0.1270). When evaluating digestibility relative to time, differences were observed (P ≤ 0.0013) at 24, 48, and 72 h. These results indicate that WCS intake was greater for the ULGCS than DP1646, and significant digestibility of either variety was not observed until 24 h of digestion.